2009
DOI: 10.1136/hrt.2009.177162
|View full text |Cite|
|
Sign up to set email alerts
|

A randomised trial of target-vessel versus multi-vessel revascularisation in ST-elevation myocardial infarction: major adverse cardiac events during long-term follow-up

Abstract: Background Few reports described outcomes of complete compared with infarct-related artery (IRA)-only revascularisation in patients with ST-elevation myocardial infarction (STEMI) and multivessel coronary artery disease (CAD). Moreover, no studies have compared the simultaneous treatment of non-IRA with the IRA treatment followed by an elective procedure for the other lesions (staged revascularisation). Methods The outcomes of 214 consecutive patients with STEMI and multivessel CAD undergoing primary angioplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
291
3
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(306 citation statements)
references
References 24 publications
6
291
3
6
Order By: Relevance
“…However, in this study the additional PCI was performed without ischaemia detection. Our findings differ from a more recent randomised trial by Politi et al [5] They showed that culprit vessel-only angioplasty was associated with the highest rate of longterm MACE compared with multi-vessel treatment. The patients scheduled for staged revascularisation (SR) experienced a similar rate of MACE compared with patients undergoing complete simultaneous (CR) treatment of nonculprit lesion.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…However, in this study the additional PCI was performed without ischaemia detection. Our findings differ from a more recent randomised trial by Politi et al [5] They showed that culprit vessel-only angioplasty was associated with the highest rate of longterm MACE compared with multi-vessel treatment. The patients scheduled for staged revascularisation (SR) experienced a similar rate of MACE compared with patients undergoing complete simultaneous (CR) treatment of nonculprit lesion.…”
Section: Discussioncontrasting
confidence: 57%
“…It is not well known whether the long-term prognosis of patients with MVD can be improved by early additional revascularisation. Results from a recent randomised, not ischaemia guided, study have suggested that the rate of long-term MACE is reduced in patients with early complete revascularisation compared with culprit vesselonly angioplasty [5].…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this study are, however, consistent with previous clinical evidence, which suggests that complete revascularization reduces future MACEs [7,9,30,31] (with associated reduced hospital re-admission costs) and also improves quality of life (according to the Seattle Angina Questionnaire) [32]. There are few well-conducted economic analyses of P-PCI, especially in the context of randomized trials.…”
Section: Comparisons With Other Studiessupporting
confidence: 71%
“…A small randomized trial was stopped prematurely due to slow recruitment [31]. In a recent randomized trial [32], 214 consecutive patients with STEMI and multivessel CAD undergoing primary angioplasty were randomized before the first angioplasty to one of three strategies: 1) culprit vessel angioplasty only; 2) staged revascularization; and 3) simultaneous treatment of nonIRAs. During a mean follow-up of 2.5 years, 42 (50.0%) patients in the 'culprit vessel angioplasty only' group experienced at least one major adverse cardiac event, 13 (20.0%) had an event in the staged revascularization group, and 15 (23.1%) in the simultaneous treatment of non-IRAs group (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%